The need for non-technical skills education in Iranian operating room practitioners: A letter to the editor - Somayeh Gheysari; Mehdi Hasanshahi; Reza Kalantari (Future of Medical Education Journal, 2025)
The operating room is a high-risk environment where non-technical skills—such as teamwork, communication, leadership, and situational awareness—play a critical role in ensuring patient safety. Research highlights that the most of adverse events in surgeries are linked to non-technical skills deficits. In recent years, the study of non-technical skills among Iranian operating room practitioners has gained attention. Research has been conducted on both operating room teams and individual practitioners. In Iran, studies on operating room practitioners have identified strengths and weaknesses in non-technical skills, with moderate teamwork levels, communication failures, and varying performance across roles. While some domains like task management score well, others, such as decision-making and leadership, require improvement. Despite the lack of standardized non-technical skills training in Iran, educational interventions have shown positive effects. Developing structured curricula and regular training programs for operating room staff is essential to enhance non-technical skills, reduce errors, and improve surgical safety. Universities and hospitals should implement educational programs to improve non-technical skills among operating room personnel and ensure surgical safety.